Partnerships for tropical conservation - Vermeulen, Sonja J.; Sheil, Douglas (2007)
Achieving effective conservation in the tropics is a global concern but implicates local people. Despite considerable rhetoric about local participation the vast majority of conservation initiatives continue to be devised and controlled by a small group of powerful, external voices. What is widely overlooked is that local people often have positive conservation goals and preferences. These overlap with global values and create a strong precedent for practice, providing the basis for strategic alliances with conservation agencies. Local people can be part of a solution, rather than of the problem, if they are given the opportunity. While as yet unfamiliar to many conservationists, partnerships with local people are working in other natural resource sectors (water, commercial forestry). Strong partnerships entail shared decision making, shared risks and a balance of rights and responsibilities between external conservation agencies and local interest groups. Partnerships are no panacea, but a real commitment to partnership offers conservation outcomes that are more ethical and often more practicable than current models.